Measuring Sipatuhar Pineapple Agrotourism as a Trigger of New Tourism Destinations in North Tapanuli Regency - Nugroho B. Sukamdani; Tatan Sukwika; Yohanes Sulistyadi; Mian Simanjuntak; Hariyadi B. Sukamdani (Enrichment : Journal of Management, 2022)
The Sipatuhar pineapple plantation has become an agrotourism development area in the North Tapanuli district, North Sumatra. Although improvements are still being carried out, the interest in the tourist area does not match the expected target. It is suspected that there is no alternative to an integrated tourism program so that tourists do not get additional tourist experiences. This study aims to develop potential new tourist destinations by developing Sipahutar pineapple agrotourism. Through this development strategy, it is hoped that there will be a choice of alternative tourist objects to anticipate the saturation of tourists. This research method uses the concept of Sustainable Tourism with a SWOT analysis approach (strengths, weakness, opportunities, threats) to explore the potential of new tourist destinations around the agro-tourism area. The results showed that there is a potential for Sipahutar pineapple agro-tourism to develop an agro-industrial tourism sector based on pineapple raw materials. In addition, there is the potential to develop new tourism such as hiking and educational tourism, nature tourism and the creative economy industry to utilize pineapple leaves as raw material for woven Wallets and Bags to encourage the economy of the surrounding community. The research's managerial implications recommend prioritizing alternative tourism objects that are visible and integrated with the Sipatuhar pineapple agrotourism area, such as sulfur hot springs, pineapple culinary tours, and panoramic tours.